The Characteristics of Pulp and Paper Made from Top Section of Betong (Dendrocalamus Asper) Bamboo by Soda Pulping Method - Mohamad Khair, Fatin Nurina; Masrol, Shaiful Rizal (Progress in Engineering Application and Technology, 2022)
This research was conducted to assess the potential of Malaysian Betong (Dendrocalamus Asper) bamboo as an alternative non-wood based material for papermaking. Top section of Betong bamboo was selected as the raw material for this study. Bamboo pulp was produced according to Soda pulping method with 25% alkali concentration (NaOH), 7:1 liquor to fibre ratio, 170 C cooking temperature and 3 hours cooking time. Malaysian International Organization for Standardization (MS ISO) and the Technical Association of the Pulp and Paper Industry (TAPPI) were referred as a standard for all process and characteristics test. Pulp characteristics have been observed as pulp moisture content (18.45%), screen yield percentage (20.88%), pulp drainage time (5.88s), and Canadian Standard Freeness (CSF) (691.5ml). For physical characteristic, thickness (578.9μm), grammage (130 gsm), and paper density (0.225 g/cm3) were observed. Mechanical characteristics also investigated by tensile index (1.581 Nm/g), tear index (1.817 mN.m2/g), burst index (1.730 kPa.m2/g), and folding endurance (1.758). The top section of Malaysian Betong bamboo virgin soda pulp and paper had shown a promising quality as papermaking material. However, more future in-depth investigation is needed to improve the quality of the pulp and paper. This study had shown the potential quality of Malaysian Betong bamboo as an alternative non wood-based material for papermaking.